Les écoles secondaires communautaires en Tanzanie : piliers d'une réforme égalitaire ou éducation de seconde zone ? - Nathalie Bonini (Les éditions de la Maison des sciences de l'Homme, 2017)
To improve school infrastructure on Tanzanian territory and increase access to secondary education, the government launched an education development program in 2004. This plan has led to the opening up of a large number of public secondary schools through the development of community schools. The so-called community schools are funded by the Tanzanian State but also largely by the citizens. They enroll pupils who scored low at the primary final examination, they also lack of financial and human resources (especially teachers) which is a major impediment to student success. While the creation of community schools raised the secondary school enrollment rates, it failed to reduce territorial and socio-economic inequalities that were operating before its implementation. A small minority of pupils enrolled in prestigious institutions (public or private) receive quality education allowing them to go on with their studies, while the community schools enrolling the majority of students lead only a few of them beyond O-Level and provide them with an education of varying quality that does not always meet their families' expectations.